(untitled) (Altre Modernità, 2013)
The study analyzes the short story “Shelter” (1964) by José Emilio Pacheco (México D.F., 1939), published in the volume La sangre de Medusa y otros cuentos marginales (1991). The apocalypse marks the narrative construction of a traumatic imaginary related with dichotomy between real and imaginary trauma. The protagonist’s fear of a Third World War produces a suspension of reality’s principle and the projection of his interiority, leading to a fracture into the story between the level of imagination and the real experience. The texts reflects the configuration of a discourse where trauma plays as the significant in the organization of subjectivity and fiction.